Survey on model checking based hardware Trojan detection technology - Qizhi ZHANG; Yiqiang ZHAO; Ya GAO; Haocheng MA (网络与信息安全学报)
Hardware Trojan is malicious tampering to the original circuit, which has become the most important security threat of integrated circuit.In order to ensure the safety and reliability of ICs, many hardware Trojan detection methods are proposed.As one of the formal verification methods, model checking can effectively detect the hardware Trojan in the design phase.Firstly, the working principle and process of model checking were described.Secondly, the research progress of hardware Trojan detection technology based on model checking was introduced.Finally, the bottlenecks faced by the current technology were pointed out and the potential research direction was discussed.